STRATEGIES FOR INTERNALIZING MORAL VALUES IN GENERATION Z THROUGH AKIDAH AKHLAK LEARNING AMID DIGITAL DISRUPTION - Nadiroh, Reva Safa’atun; Noviriani; Mabruri; Farizi, Ahmad Al; Yani, Ahmad; Adilla, Ulfa (Irfani, 2023)
Generation Z students in Indonesian madrasah are growing up in a learning environment saturated with social media, short-form video, and algorithmically curated content, conditions that have shifted how they encounter and weigh moral information. This study examined how Akidah Akhlak teachers internalized moral values amid such digital disruption at Madrasah Tarbiyah Islamiah, Bungo Regency, Jambi Province, Indonesia. A qualitative case study was conducted between July and October 2025 with 8 teachers and 15 Grade IX students; data were collected through 24 classroom observations, semi-structured interviews recorded with a Sony ICD-PX470 voice recorder (±0.01% time-base accuracy), and document analysis of lesson plans and assessment artifacts. Transcripts were coded thematically using a constant-comparison procedure, with inter-rater agreement at Cohen’s kappa = 0.83 across two coders. Four operative strategies emerged: Islamic digital literacy, teacher exemplarity (uswah hasanah), technology-based spiritual habituation, and adaptive curriculum integration. The proportional distribution across 24 sessions showed direct exemplarity at 28%, digital storytelling at 22%, group reflection at 18%, Quranic-text contextualization at 16%, and habituation routines at 16%. A four-stage workflow (diagnostic, content design, classroom enactment, reflective evaluation) supported coherent application of these strategies and fed iterative refinement into subsequent cycles. The findings indicate that internalization works best when digital pedagogy and prophetic exemplarity reinforce one another rather than compete. The study contributes a context-grounded operational template for moral education in madrasah settings facing accelerating digital pressures and offers a basis for future quasi-experimental testing of strategy combinations